Laparoscopic Resection Verses Transvaginal rResection in the Management of Exogenous Cesarean Scar Pregnancy (Global Journal of Medical Research, 2018)
Abstract not found
Keywords: exogenous caesarean scar pregnancy; laparoscopic resection; transvaginal resection